Quantitative Infrared Spectroscopy for Understanding of a Condensed Matter - Hasegawa, Takeshi (Springer Japan : Imprint: Springer, 2017)
This book is intended to provide a course of infrared spectroscopy for quantitative analysis, covering both bulk matter and surface/interface analyses. Although the technology of Fourier transform infrared (FT-IR) spectroscopy was established many years ago, the full potential of infrared spectroscopy has not been properly recognized, and its intrinsic potential is still put aside. FT-IR has outstandingly useful characteristics, however, represented by the high sensitivity for monolayer analysis, highly reliable quantitativity, and reproducibility, which are quite suitable for surface and interface analysis. Because infrared spectroscopy provides rich chemical information-for example, hydrogen bonding, molecular conformation, orientation, aggregation, and crystallinity-FT-IR should be the first choice of chemical analysis in a laboratory. In this book, various analytical techniques and basic knowledge of infrared spectroscopy are described in a uniform manner. In particular, techniquesfor quantitative understanding are particularly focused for the reader's convenience.